Effects of low-frequency rTMS combined with antidepressants on depression in patients with post-stroke depression: a systematic review and meta-analysis - Pan, Juanhong; Li, Hongpeng; Wang, Yongshen; Lu, Li; Wang, Ying; Zhao, Tianyu; Zhang, Di; Jin, Song (Frontiers in Neurology, 2023)
Objective To evaluate the effect of low-frequency (≤1 Hz) repetitive transcranial magnetic stimulation (low-frequency rTMS) combined with antidepressants on depression and the levels of inflammatory factors IL-6 and TNF-α in patients with post-stroke depression (PSD). Design PubMed, Embase, Web of Science, Cochrane Library (CBM), China National Knowledge Infrastructure, Technology Periodical Database, and Wanfang Database were searched until October 2022 for randomized controlled trials. Participants Patients with post-stroke depression (PSD) participated in the study. Results A total of 16 randomized controlled trials (RCTs) involving 1,463 patients with PSD were included. According to the Physiotherapy Evidence Database (PEDro) quality assessment, three studies received high quality (eight scores) and 13 RCTs received moderate quality (six scores) results. The meta-analysis showed that low-rTMS combined with an antidepressant significantly reduced the Hamilton Depression Scale (HAMD) score and the National Institutes of Health Stroke Scale (NIHSS) score, reduced IL-6 and TNF-α levels, and improved the MMSE score in PSD compared to an antidepressant alone. Conclusion The results of this meta-analysis evidenced the efficacy and safety of low-rTMS combined with antidepressants in the treatment of depression in PSD patients. The combined therapy could reduce The depression state and the levels of IL-6 and TNF-α, and enhance the cognitive function of patients. In addition, low-rTMS had fewer adverse effects, proving safety. However, there are shortcomings, such as a lack of long-term follow-up, different intervention sites of low-rTMS, and different intervention frequencies (0.5 or 1 Hz). Thus, in the future, RCTs with a larger sample size and longer-term observation are required to verify the efectiveness of low-rTMS combined therapy on PSD. Meantime, a new meta-analysis could be analysized, which intervention sites and frequency are more effective in treating PSD. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022376845.